Formation of Tough Films by Evaporation of Water from Dispersions of Elastomer Microspheres Crosslinked with Rotaxane Supramolecules. Issue 35 (5th June 2017) - Hiroshige, Seina; Kureha, Takuma; Aoki, Daichi; Sawada, Jun; Aoki, Daisuke; Takata, Toshikazu; Suzuki, Daisuke
Abstract: Compared to rigid microspheres that consist, for example, of polystyrene or silica, soft and deformable elastomer microspheres can be used to generate colorless transparent films upon evaporating the solvent from microsphere‐containing dispersions. To obtain tough films, a post‐polymerization reaction to crosslink the microspheres is usually necessary, which requires extra additives during the drying process. This restriction renders this film‐formation technology complex and rather unsuitable for applications in which impurities are undesirable. In the present study, it is demonstrated that tough elastomer microspheres that are crosslinked with rotaxanes can form tough bulk films upon evaporation of water from microsphere dispersions, so that post‐polymerization reactions are not required. The results of this study should thus lead to new applications including coatings for biomaterials that need complete removal of all impurities from the materials prior to use. Abstract : The tough get going : Rotaxane‐crosslinked elastomer microspheres are generated by mini‐emulsion polymerization. Evaporating the water from dispersions of these microspheres affords tough films with higher fracture strain and stress values than films of microspheres without crosslinkers or of microspheres crosslinked by conventional crosslinkers. The increased fracture strain and stress values are attributed to stress relaxation originating from the flexibility of the rotaxane crosslinkers.